Persepsi Peserta Terhadap Aplikasi Mobile JKN Berbasis Technology Acceptance Model Di Klinik Pratama Surya Medika Semarang - Harsono Harsono; Sigit Sugiharto; Rinayati Rinayati (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
The JKN Mobile Application is an application designed by BPJS Health to balance the current increasing use of mobile technology and to provide easy acces and convenience for JKN participants online. This study aims to determine the extent to which JKN participants perceptions of the JKN Mobile Application are measured using the TAM (Technology Acceptance Model) analysis model based on the usefulness (perceived usefulness) and ease of use (perceived ease of use) This research is a quantitative descriptive study using a cross-sectional research design with a research sample of 38 JKN participants registered at the Pratama Surya Medika Clinic Semarang through random sampling with the research instrument used is a questionnaire. The results showed that the overall JKN mobile application was rated 82,5% as very useful and 84% very easy to operate so it was very helpful and supportive for JKN participants in getting health services at the Pratama Surya Medika Clinic Semarang Keywords: JKN Participant Perception, JKN Mobile Application, TAM (Technology Acceptance Model)